The Geopolitical Chessboard: How India-China Rivalry Shapes South Asian Politics - Santa Bahadur Thapa (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
The emergence of the geopolitical scene of China and India is shaking up the world. China is a global manufacturing giant that has bolstered economies as they recover; India, the world’s largest democracy, is one of the fastest-growing economies in the world. The paper discusses the complex and nuanced challenge that the India-China rivalry presents to South Asian politics. It examines the dynamics of their relationship, their influence within international organisations, and the implications of their contestation for the domestic and foreign policies of South Asian states. Based on a qualitative research design, this study comprises an examination of historical narratives, case studies of select South Asian countries, and an analysis of geopolitical constructs and theories. The India-China rivalry has a significant impact on regional alliances, security concerns, and the application of soft power and cultural diplomacy in South Asia, according to the findings